2020
DOI: 10.1155/2020/4256301
|View full text |Cite
|
Sign up to set email alerts
|

Identification of COVID-19 Infection-Related Human Genes Based on a Random Walk Model in a Virus–Human Protein Interaction Network

Abstract: Coronaviruses are specific crown-shaped viruses that were first identified in the 1960s, and three typical examples of the most recent coronavirus disease outbreaks include severe acute respiratory syndrome (SARS), Middle East respiratory syndrome (MERS), and COVID-19. Particularly, COVID-19 is currently causing a worldwide pandemic, threatening the health of human beings globally. The identification of viral pathogenic mechanisms is important for further developing effective drugs and targeted clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 52 publications
0
15
0
2
Order By: Relevance
“…Pathway enrichment analysis revealed biological processes involved in host immune function (e.g., immune effector process, cellular response to cytokine stimulus, cytokine-mediated signaling pathway, response to biotic stimulus, cytokine, other organism, external biotic stimulus,) and the response to viruses (e.g., viral process, defense response to virus and other organism). These biological processes have been suggested to have critical roles in the pathogenesis of coronavirus infections [46][47][48]. Lymph nodes maintain and coordinate new immune responses to control the viruses, although age-related lymph nodes changes reduce the ability of B and T cells to proliferate and differentiate in lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Pathway enrichment analysis revealed biological processes involved in host immune function (e.g., immune effector process, cellular response to cytokine stimulus, cytokine-mediated signaling pathway, response to biotic stimulus, cytokine, other organism, external biotic stimulus,) and the response to viruses (e.g., viral process, defense response to virus and other organism). These biological processes have been suggested to have critical roles in the pathogenesis of coronavirus infections [46][47][48]. Lymph nodes maintain and coordinate new immune responses to control the viruses, although age-related lymph nodes changes reduce the ability of B and T cells to proliferate and differentiate in lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…With the available scientific approaches and computational facilities to model proteins and investigate proteinligand interactions it becomes more supportive to predict the binding of small molecular drugs to protein targets [28,37,38]. Employing density functional theory [39] the geometry of all the molecules proposed as COVID-19 drug candidates, were optimized to understand structural features and hence their contribution to the inhibition or druggable potential.…”
Section: Introductionmentioning
confidence: 99%
“… 16 , 17 It has recently been shown that one of the main mechanisms of virus pathogenesis is targeting key human genes and suppressing their expression through viral miRNAs. 18 Therefore, study of viral microRNAs allows us to become more familiar with mechanism of coronavirus pathogenesis. In fact, viral microRNAs play a role in completing virus life cycle.…”
Section: Introductionmentioning
confidence: 99%